USULAN RANCANGAN TATA LETAK FASILITAS DENGAN PENDEKATAN ERGONOMI GUNA MENGURANGI AKTIVITAS FISIK DI INDUSTRI MANUFAKTUR BETON PRECAST KOTA CILEGON - Rini, Asih Setyo; Varina, Eka Lailita Eti; Muhammad, Irfan; Khaerudin, Dedy; Rahmatullah, Asep; Wirabuana, Setyo Fiddin (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
The significant development of the manufacturing industry has led to increasingly complex problems that can occur. Inappropriate facility layout can affect excessive physical activity, so that the activities carried out are not optimal. Ergonomic facility layout design directs the arrangement of physical facilities (machines and equipment) to obtain the fastest production process by minimizing physical activity. The precast concrete manufacturing industry in Cilegon City has an area of ​​623.65 m2, which consists of worker facilities, physical facilities (machines and equipment) and structural position facilities. Environmental conditions that are less flexible and poor placement between facilities (far from the reach of their duties) greatly affect workers' physical activity. This, intends to propose a facility layout design with an ergonomic approach using several CORELAP (Computerized Relation Layout Planning) and ARC (Activity Relation Chart) methods. The conclusions from this processing and analysis are based on proximity codes A, E, I U and O. Keywords: Ergonomic, Fisiologi